The effect of first and second language use on question types in English medium instruction science classrooms in Hong Kong - Pun, J; Macaro, E (Taylor and Francis, 2018)
The role of the first language (L1) in second language (L2) learning has been widely discussed and researched in the second Language Acquisition (SLA) literature. Benefits of L1 use have been found for vocabulary acquisition, and in facilitating comprehension thereby alleviating student anxiety. Many teachers appear to consider L1 use as a necessary option in L2 pedagogy. Disadvantages of L1 use are argued to be that it reduces exposure to the L2 thereby not enabling more implicit forms of L2 acquisition. Considerably less research has been carried out in English medium instruction (EMI) classrooms, surprisingly, as these are predicated on the benefits of massive exposure to the L2. This study investigated the effect of L1 and L2 use on teacher question types and interaction patterns in science lessons in early EMI and late EMI schools in Hong Kong. Our findings show that in late EMI, where there was much greater use of the L1, teachers tended to use higher order questions and were more interactive. In early EMI, despite students having received four more years of greater exposure to English instruction than late EMI students through the use of English as the vehicular language, teachers asked lower order questions and the interaction was more monologic. The implications for policy and pedagogy are discussed.